Study of a Turkey Population for Gene Preservation - Szőke, Szilvia; Komlósi, István; Korom, Edit; Ispány, Márton; Mihók, Sándor (Acta Agraria Debreceniensis, 2004)
Genetic variability is very important in small populations. We examined an indigenous bronze turkey population which is bred for gene conservation in order to see if the current mating system maintains genetic variability. The present generation was surveyed using microsatellite markers and a computer model was used to simulate changes in the population over 100 generations.The data was analysed using the concept of entrophy from information theory instead of genetic variance so that we could more accurately measure genetic variability.The results indicate that the breeding method currently in use, rotational line mating, is acceptable with respect to preserving genetic variability, but new selection methods may provide additional protection against the loss of alleles.